Islamic activism: a social movement theory approach - Wiktorowicz, Quintan (Indiana series in Middle East studies, 2004)
Islamic activism and social movement theory / Quintan Wiktorowicz -- From marginalization to massacres : a political process explanation of GIA violence in Algeria / Mohammed M. Hafez -- Violence as contention in the Egyptian Islamic movement / Mohammed M. Hafez and Quintan Wiktorowicz -- Repertoires of contention in contemporary Bahrain / Fred H. Lawson -- Hamas as social movement / Glenn E. Robinson -- The networked world of Islamist social movements / Diane Singerman -- Islamist women in Yemen : informal nodes of activism / Janine A. Clark -- Collective action with and without Islam : mobilizing the bazaar in Iran / Benjamin Smith -- The islah party in Yemen : political opportunities and coalition building in a transitional polity / Jillian Schwedler -- Interests, ideas, and Islamist outreach in Egypt / Carrie Rosefsky Wickham -- Making conversation permissible : Islamism and reform in Saudi Arabia / Gwenn Okruhlik -- Opportunity spaces, identity, and Islamic meaning in Turkey / M. Hakan Yavuz -- Social movement theory and Islamic studies / Charles Kurzman